Environmental sustainability, decision-making, and management for mineral development in the Canadian Arctic. Issue 4 (18th May 2020) - Collins, B.; Kumral, M.
ABSTRACT: The Canadian Arctic is a complex and fragile region which is currently experiencing unprecedented environmental degradation due to climate change. The effects of climate change on the Canadian Arctic is just one example where we're seeing the decline of ecosystems and socio-culture-environmental traditions. Mineral development in this already fragile ecosystem is indeed a contentious and high-risk endeavour. However, mining is currently one of the few industries and economic development opportunities in the Canadian Arctic, which is one of the poorest regions in Canada. Unfortunately, mining struggles to achieve environmental sustainability due to mineral development's inherent trade-off of short-term economic gains for long-term environmental impacts. Local communities are usually left with trying to find this balance. This paper analyzes how we can apply decision-making techniques and environmental management tools for the Canadian Arctic's mining industry to promote better environmental sustainability, understanding of environmental-economic trade-offs, and community involvement. Specific decision-making methodologies and management tools are analyzed to develop, discuss, and explore their application for the Canadian Arctic. This paper concludes with a framework that brings together the analyzed methods and Arctic specificities; to prioritize environmental issues and to ensure long-term thriving communities in the Arctic.